Highly thermally conductive 3D BN/MWCNTs/C spatial network composites with improved electrically insulating and flame retardancy prepared by biological template assisted method. (1st October 2021) - Pan, Duo; Luo, Shilu; Feng, Yao; Zhang, Xiaodong; Su, Fengmei; Liu, Hu; Liu, Chuntai; Mai, Xianmin; Naik, Nithesh; Guo, Zhanhu
Abstract: Boron nitride/multiwalled carbon nanotubes/carbon (BN/MWCNTs/C) networks were prepared via a rape pollen (RP) biological template assisted strategy. The highly thermally conductive epoxy resin (EP) composites were prepared by impregnating EP into the 3D BN/MWCNTs/C networks. Fourier transform infrared spectra and X-ray photoelectron spectroscopy analyses indicated that the successful modification of BN (m-BN) and the interaction between RP, carboxyl functionalized MWCNTs (c-MWCNTs) and m-BN. Scanning electron microscopy images clearly present the network morphology constructed by MWCNTs connected to m-BN. Thermogravimetric analyzer curves determine the mass concentration of m-BN in EP-based composites. The thermal conductivity ( K ) reached 1.84 W/(m·K) in the composites at a BN content of 21.3 wt%, displaying a significant enhancement of 868% compared with pure EP. The enhanced K is attributed to the effective connection of BN by the MWCNTs covered on the surface of RP. Meanwhile, the composites exhibit a tensile strength of 39.2 MPa, electrically insulating with a volume electrical resistivity about 9.17 × 10 10 Ω cm and good flame retardancy. Graphical abstract: Image 1 Highlights: 3D BN/MWCNTs/C thermal conductive networks were prepared via a biological template assisted strategy. Epoxy-based composites were prepared by a vacuum-assisted impregnation method. Thermal conductivity was significantly enhanced in this system. Electrical insulation and flame retardancy performances were observed as well.